1982
DOI: 10.1111/j.1471-4159.1982.tb07896.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in the Activity Ratio of Specific and Nonspecific Cholinesterases from Neuronal Perikarya

Abstract: A soluble fraction from rat brain neuronal perikarya was shown to contain both the specific and nonspecific forms of the enzyme acetylcholinesterase (EC's 3.1.1.7. and 3.1.1.8., respectively). The ratio of the enzyme activities varied along the course of brain development: the nonspecific form being predominant from 1 to 15 days of age and the specific one showing the pattern of rising activity from day 15 onward. We suggest a possible relationship between this changing in cholinesterase activities and the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…In the absence of any biochemically verifiable interaction with membrane lipids, it is difficult to reconcile our results with those hypotheses linking BuChE with any significant membrane-associated function, be it in glia or neuron (Davis and Koelle, 1978;Graybiel and Ragsdale, 1982;Ochoa et al, 1982). Nor are these data consistent with any simple interconvertibility of the two enzymes (Koelle et al, 1979), at least in CNS tissue.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…In the absence of any biochemically verifiable interaction with membrane lipids, it is difficult to reconcile our results with those hypotheses linking BuChE with any significant membrane-associated function, be it in glia or neuron (Davis and Koelle, 1978;Graybiel and Ragsdale, 1982;Ochoa et al, 1982). Nor are these data consistent with any simple interconvertibility of the two enzymes (Koelle et al, 1979), at least in CNS tissue.…”
Section: Resultscontrasting
confidence: 75%
“…Also, according to Graybiel and Ragsdale (1982), BuChE in the monkey brain shows a distinct neuronal localization that is different from that of AChE, suggesting that the enzyme or its substrate may act as a neuroactive substance in the primate visual system. Similarly, Ochoa et al (1982) have shown that BuChE activity is present, albeit in low activity, not only in isolated neuronal peri-karya, but in synaptosomal and microsomal fractions as well.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation